Partisipasi Politik Masyarakat pada Pemilihan Umum Presiden dan Wakil Presiden Tahun 2019 - Mega Sulistiowati; Mohammad Hasan Bisyri (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Political participation is the activity of a person or group of people to be actively involved in politics, namely choosing the leadership of the state together directly or indirectly. These activities include making choices during elections, attending political party campaigns and becoming a member of politics or mass organizations. General Election Commissions (KPU) of Pekalogan City in carrying out its duties to increase public political participation in the 2019 presidential and vice presidential elections is in accordance with what is described in the General Election Commission Regulation of the Republic of Indonesia Number 10 of 2018 concerning Socialization, Voter Education, and Community Participation in the Implementation of General Elections. The formulation of the problem: (1) How did the General Election Commission (KPU) of Pekalongan City in the 2019 Presidential and Vice Presidential Elections achieve the target of 84.02% public participation? (2) What are the supporting and inhibiting factors for public participation in the 2019 Presidential and Vice-Presidential Elections? This study uses field research, using a qualitative approach. This type of research uses empirical juridical. The results of this study indicate that the efforts of the Pekalongan KPU can be said to be successful in achieving the target of community participation. One of the factors influencing the increase in participation is strategy. The strategy carried out consists of a short-term strategy and a long-term strategy.